Ionising radiation: risks/benefits or costs/benefits? - Failla, Lidia (Medicina e Morale, 1989)
Ionizing radiation (r. i.) as it is known poses a risk of harm to humans. Such radiation is present in a considerable number of activities, especially in the medical field (x-rays, in all their varied applications such as: x-rays, scopes, CT scans, etc. nuclear medicine: diagnostics and therapy).